2017
DOI: 10.21315/jcdc2017.22.supp1.5
|View full text |Cite
|
Sign up to set email alerts
|

Time Delay and Cost Overrun of Road over Bridge (ROB) Construction Projects in India

Abstract: This paper aims at studying the factors that contribute to time delay and cost overrun of Road over Bridge (ROB) projects in India. Data for the research study were collected from 62 respondents, including owners, contractors, and consultants of ROB projects. The literature survey and the questionnaire survey helped in identifying 29 factors. The topmost factors were ranked based on the frequency of occurrences. The correlation among owners, contractors, and consultants on ranking of factors was derived by Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…The first stage of synthesizing the 152 literatures is dividing them according to 2 classifications, literatures from the developed countries and literatures from developing countries as presented in Table 2 & 3. (Afzal et al, 2019;Anish et al, 2019;Bhangale, 2016;Chandramohan et al, 2012;Cindrela Devi & Ananthanarayanan, 2017;Ghumare et al, 2019;Kant, 2018;Muthu Venkata Sekar & Mahalakshmi, 2018;Pai et al, 2018;Raju et al, 2017;Shaktawat & Vadhera, 2017;Shanmuganathan & Baskar, 2015;Sharma et al, 2020;Sharma & Goyal, 2019;Shrivastava et al, 2019;Subramani & Sivakumar, 2018;Velumani & Nampoothiri, 2019;Venkateswaran & Murugasan, 2017;Wanjari & Dobariya, 2016) Malaysia 20 (Abdullah et al, 2018;Afzal et al, 2019;Akram et al, 2017;Asmi et al, 2013;Azis et al, 2013;Hameed Memon et al, 2014;Haslinda et al, 2018;Ismail et al, 2013;Karunakaran et al, 2018;Liew et al, 2019;Memon et al, 2011Memon et al, , 2012Rahman et al, 2013;C. Ramanathan et al, 2012;C.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…The first stage of synthesizing the 152 literatures is dividing them according to 2 classifications, literatures from the developed countries and literatures from developing countries as presented in Table 2 & 3. (Afzal et al, 2019;Anish et al, 2019;Bhangale, 2016;Chandramohan et al, 2012;Cindrela Devi & Ananthanarayanan, 2017;Ghumare et al, 2019;Kant, 2018;Muthu Venkata Sekar & Mahalakshmi, 2018;Pai et al, 2018;Raju et al, 2017;Shaktawat & Vadhera, 2017;Shanmuganathan & Baskar, 2015;Sharma et al, 2020;Sharma & Goyal, 2019;Shrivastava et al, 2019;Subramani & Sivakumar, 2018;Velumani & Nampoothiri, 2019;Venkateswaran & Murugasan, 2017;Wanjari & Dobariya, 2016) Malaysia 20 (Abdullah et al, 2018;Afzal et al, 2019;Akram et al, 2017;Asmi et al, 2013;Azis et al, 2013;Hameed Memon et al, 2014;Haslinda et al, 2018;Ismail et al, 2013;Karunakaran et al, 2018;Liew et al, 2019;Memon et al, 2011Memon et al, , 2012Rahman et al, 2013;C. Ramanathan et al, 2012;C.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Time delays are common in all types of construction projects, and they are more project-specific (Venkateswaran & Murugasan, 2017). Venkateswaran & Murugasan (2017) in their paper assessed the causes of time delay in Road Over Bridge (ROB) projects in India.…”
Section: Legal and Social Factors And Organization Managementmentioning
confidence: 99%
“…Time delays are common in all types of construction projects, and they are more project-specific (Venkateswaran & Murugasan, 2017). Venkateswaran & Murugasan (2017) in their paper assessed the causes of time delay in Road Over Bridge (ROB) projects in India. This study found that among the 29 factors, the major causes were land acquisition, an extra number of stakeholders, displacement of network disputes and claims, and legal requirements.…”
Section: Legal and Social Factors And Organization Managementmentioning
confidence: 99%
“…There are also different causes for poor performance by the contractor such as poor project management and control, low efficiency and poor planning. Therefore, the problems can be reduced through joint efforts of stakeholders in the industry (Venkatesh et al , 2012; Venkateswaran and Murugasan, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%